PECULIARITIES OF WORK WITH A CLIENT’S REQUEST AT MULTIMODAL SUGGESTIVE PSYCHOTHERAPY - Manilov, Igor (PSYCHOLOGICAL JOURNAL, 2019)
The article represents the peculiarities of work with a client’s request at Multimodal Suggestive Psychotherapy. It shows that such peculiarities of work with a client’s request are caused by specificity of the main theoretical statements of Multimodal Suggestive Psychotherapy. These theoretical statements are based on the ideas represented in the concept of adaptive suggestive modification of thinking. The article contains the data obtained during individual psychotherapeutic sessions with 348 clients. The recorded cases were compiled with the clients having neurotic and somatoform disorders caused by stress, as well as having non-complicated affective disorders, mature personality disorders and some behavioural syndromes (sex dysfunction; disorders of sleep, eating behaviour). The article determines that a client’s request must be correlated with the basic modalities of Multimodal Suggestive Psychotherapy, such as: «mental status», «cognitive processes», «state of soma», «reflex impulses-actions», «actual needs», «overcoming strategies». This procedure allows an applied psychologist to extend a list of conditionally pathogenic factors of client’s vital functions and to identify the actual profile of an examined problem. This profile sets the local strategy of work within every specific psychotherapeutic session. Averaged local profiles of the examined problem allows an applied psychologist to formulate a strategic request and to determine a general vector of multimodal suggestive psychotherapeutic influence. The article notes the specific and cyclic nature of work with a client’s request at Multimodal Suggestive Psychotherapy. Such cyclicity reveals itself in permanent transitions from general formulations to the most concrete ones and vice versa. A client’s request processing enables corrections of false formulations and eliminates consequences of different cognitive biases. While working with a client’s request using Multimodal Suggestive Psychotherapy, it is necessary to take into account such sources of cognitive biases as: “self-centric” consciousness; quasi-accomplished conclusions; spontaneous reduction of cognitive structures. The cognitive bias influence on a client’s request at Multimodal Suggestive Psychotherapy can be decreased by means of the psychotherapeutic confrontational suggestion method.